Kreativitas Guru Melibatkan Ragam Model Pembelajaran dalam Kegiatan Pembelajaran Matematika terhadap Keberhasilan Belajar Siswa di Sekolah Dasar - Eka Rosmitha Sari; Hijrawatil Aswat; Mitra kasih La Ode Onde; Fitriani B; Mitra Purnama (Journal on Education, 2023)
The purpose of this study is to further examine teacher creativity in involving various learning models in mathematics learning activities and how student learning success rates are viewed from cognitive, affective, and psychomotor aspects. This research is a qualitative research involving students and teachers of class V as research subjects. The research instrument uses observation sheets of learning activities, interview guidelines, and student learning outcomes tests. Three types of activities in data analysis are data reduction, data display, and conclusions. The results showed that there are four steps or stages of teacher activities in presenting meaningful learning activities for students including, first the planning stage (developing lesson plans, matching learning models with learning objectives to be achieved, teaching aids, learning media, learning resources, and evaluation procedures). Second, the stage of preparing or completing everything that has been planned (the availability of syllabus, lesson plans, mathematics subject matter that is integrated with other subject matter that is netted in sub-themes, learning media, learning scenarios to make it easier for teachers to succeed the learning model involved, evaluation tools in the form of student worksheets). Third, the implementation stage, namely teacher creativity in carrying out learning in the classroom including variations in teaching styles, material presentation patterns, interaction patterns, strengthening student understanding, selection of learning media, selection and determination of learning models. Fourth, the evaluation stage through 3 aspects, namely the cognitive aspect by providing LKS to students as a standard for material ability and understanding, affective aspects through the observation sheet of social and spiritual attitudes that have been provided by the teacher, and psychomotor aspects are evaluated during the learning process where the teacher provides evaluation in performance both in the form of work and the ability of students to implement mathematical knowledge in everyday life. From the creativity of this teacher, it shows the success of student learning from cognitive, affective, and psychomotor aspects with an average classical completeness of ≥80%.